2008
DOI: 10.1111/j.1365-2095.2007.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative intestinal absorption of amino acids in rainbow trout (Oncorhynchus mykiss), totoaba (Totoaba macdonaldi) and Pacific bluefin tuna (Thunnus orientalis)

Abstract: The kinetics of amino acid absorption in the proximal section of three fish species were studied using an everted intestine technique and a pancreatic digest of casein (Tryptone), as the model amino acid mixture. Fresh intestine of rainbow trout (Oncorhynchus mykiss) was used to set up the experimental system, and results were compared with those obtained using intestines from totoaba (Totoaba macdonaldi) and bluefin tuna fish (Thunnus orientalis). The kinetics of amino acid absorption was sigmoidal for all am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Indeed, Nordrum et al (2000) found higher amino acid absorption rates in Atlantic salmon and trout in marine environment than in freshwater environment. On the contrary, Rosas et al (2008) found that absorption rates in trout were 10-fold those of tuna. As previously mentioned, the use of different approaches such as the use of buffers containing individual amino acids or amino acid premixes, respectively avoiding or evidencing the competition phenomena for the transporter active sites, may be one of the causes of the divergence of results.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, Nordrum et al (2000) found higher amino acid absorption rates in Atlantic salmon and trout in marine environment than in freshwater environment. On the contrary, Rosas et al (2008) found that absorption rates in trout were 10-fold those of tuna. As previously mentioned, the use of different approaches such as the use of buffers containing individual amino acids or amino acid premixes, respectively avoiding or evidencing the competition phenomena for the transporter active sites, may be one of the causes of the divergence of results.…”
Section: Discussionmentioning
confidence: 88%
“…3) Moreover, free amino acids, as supplied in PP75 and PP100 diets, have higher average availability than protein-bound amino acids, leading to an asynchronous utilisation when amino acids from different origins are present in the meal (Ambardekar et al, 2009). The ensemble of these modifications could be responsible for the previously hypothesised modification of luminal nutrient abundance and the consequent variation of amino acid transport rates because of competition or inhibition phenomena, as suggested by Rosas et al, (2008). Likewise, histopathological modifications previously described in salmonids (Baeverfjord and Krogdahl, 1996;Krogdahl et al, 2003) and sea bream (Sitjà-Bobadilla et al, 2005;Santigosa et al, 2008) fed plant protein-based meals could be partially responsible for this transport modulation since transporters are immersed in the lipid bilayer and diffusion and absorption efficiency are affected by bilayer characteristics (Houpe et al:, 1997;Spektor and Yorek, 1985) and enterocyte development (Smith, 1993).…”
Section: Discussionmentioning
confidence: 92%
“…This uses segments from different parts of the intestine maintained in oxygenated Ringer solution to measure the movement of molecules across the cellular membrane barrier under different conditions. In combination with pH-stat, it has been used to assess differences in the absorption of amino acids after hydrolysis of different proteins in different fish species (Rosas et al 2008;Mart ınez-Montaño et al 2010). Nevertheless, such a configuration can be considered a combination of in vitro and in vivo techniques and tends to be quite complex because the intestinal portion must be maintained alive using specialized equipment.…”
Section: Configurationsmentioning
confidence: 99%
“…In combination with pH‐stat, it has been used to assess differences in the absorption of amino acids after hydrolysis of different proteins in different fish species (Rosas et al . ; Martínez‐Montaño et al . ).…”
Section: In Vitro Digestion Models and Approaches Used With Aquatic Amentioning
confidence: 99%
“…Nevertheless, totoaba breeding programmes currently underway in Northwest Mexico have succeeded in the production of fry for the purpose of stock enhancement, as well as for the development of aquaculture. So far, research with the species has focused on its nutritional requirements and various aspects of its biology and physiology in captivity (Rosas, V azquez-Duhalt, Tinoco, Shimada, D'Abramo & Viana 2008;Rueda-L opez, Lazo, Correa & Viana 2011;Minjarez-Osorio, Gonz alez-F elix & Perez-Velazquez 2012;Badillo-Zapata, Lazo, Herzka & Viana 2014;L opez, Flores-Ibarra, Bañuelos-Vargas, Galaviz & True 2015).…”
mentioning
confidence: 99%